Legal personality of natural persons in the Czech medieval private law: Brief Summary - Vilém Knoll (Journal on European History of Law)
This article explores legal personality within a hierarchical society, examining the factors influencing an individual's rights and obligations. It discusses the significance of social position, age, creditworthiness, sex, and honour in determining an individual's legal capacity. The article highlights the limited social mobility within the hierarchical structure, the importance of the age of majority, the implications of honour and reputation, the role of women in the legal system, and the impact of disabilities and non-Christian faiths. Additionally, it touches on using names and aristocratic predicates to indicate social status. The article provides a concise overview of the complex dynamics surrounding legal personality in historical contexts.